Current Distribution of a Luxurious Wood Species, Diospyros spp. with Its Climatic Information, based on Global Biodiversity Website - Eko Prasetyo; Singgih Utomo; Ahdiar Fikri Maulana; Ridla Arifriana; Puji Lestari (Jurnal Sylva Lestari, 2022)
Ebony (Diospyros spp.) is a fancy wood distributed in eastern Indonesia. D. celebica Bakh, D. lolin Bakh, D. pilosanthera Blanco, D. ebenum Koenig, D. ferrea (Wild.) Bakh and D. rumphii Bakh are categorized as "Fancy Wood Class I" in the Indonesian market. These woods are an important product with the highest tax compared to other grades. This study aimed to identify the distribution of six ebonies based on data global biodiversity web service (Global Biodiversity Information Facility) and their climatic condition based on global climate data (WorldClim). Data from the web service, species occurrence, and climatic conditions were processed using QGIS. Species occurrence data was then extracted using GBIF occurrence. Furthermore, species occurrence data was then overlaid with climate data using point sampling tools. The results found that three ebonies scattered in the tropics and three others (D. celebica Bakh, D. rumphii Bakh, D. lolin Bakh) mostly occurred in Indonesia. Annual rainfall and temperature conditions ranged from 1,722 − 4,013 mm and 23.4 − 27.2°C for the three species of ebony in Indonesia. The distribution and climatic conditions of ebony are the initial information for further research, such as the species distribution model related to climate change and the genetic conservation agenda. Keywords: ebony, global data, occurrence data, precipitation, temperature